MODEL KALIBRASI DENGAN PENDEKATAN WAVELET DAN PARTIAL LEAST SQUARE SERTA PENERAPANNYA DENGAN OSS-R - Ana, Elly; chamnidah, Nur; Saifudin, Toha; Atiqi, Aniq; Erfiana, Erfiana (MATEMATIKA, 2011)
Determination process of active compound concentration which contained by a drug plant quantitatively and qualitative can know by HPLC (High Performance Liquid Chromatography) and FTIR (Fourier TrasformInfrared) Â methods. Calibration aim to find relation between a group of size measure which is relative reached and cheap with a group of other size measure which is difficult and relative costly. Measurement of FTIR was done by nsampel at pwaves number. Based on these information, problems occur because the number of predictor bigger thanthe number of perception, so that require to reduce dimension. Discrete Wavelet Transform (DWT) can reduce dimension become new variables.Â with . But, result of reduction still have high collinearity between coefficients of wavelet.Partial Least Squares (PLS) can be the good solving for the problems. Combining of DWT and PLS methods on calibration models use OSS-R give a good criterion of model .